Combining different types of highly parallelised technology datasets for bioinformatic analysis in the context of biomarker discovery for tuberculosis disease and treatment response - Maasdorp, Elizna (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.